Compensation Inconsistencies in Land Acquisition for Public Interest in Indonesia - Sugiharto; Manuel Valencia Albeti Susanto (YURIS: Journal of Court and Justice, 2026)
Land acquisition for public purposes constitutes a critical instrument supporting Indonesia's national development, yet persistent inconsistencies in compensation determination undermine property rights protection and social justice objectives. This normative legal research examines the regulatory framework governing compensation and analyzes implementation gaps through detailed case study of Surabaya District Court Decision Number 1090/Pdt.G/2023/PN Sby. Employing statutory, conceptual, and analytical approaches, the study investigates how Law Number 2 of 2012 and Presidential Regulation Number 19 of 2021 translate into practice. Findings reveal that implementation suffers from formalistic interpretation prioritizing administrative documentation over substantive rights recognition. Four interconnected factors drive compensation inconsistencies: divergent legal interpretation in determining eligible recipients, inadequate transparency in appraisal procedures, structural misalignment between formal requirements and informal land transaction realities, and insufficient oversight coupled with limited public legal awareness. These deficiencies generate horizontal conflicts between registered owners and actual possessors, vertical tensions between communities and government authorities, development project delays, and perpetuation of displacement-induced poverty. Analysis demonstrates compensation disputes arise not solely from valuation disagreements but from fundamental questions regarding legitimate stakeholder identification and meaningful participation in deliberation processes. The study concludes that effective reform requires legislative clarification of ambiguous provisions, institutional capacity development for implementing authorities, transformation of deliberation mechanisms into genuine participatory forums, establishment of independent oversight bodies, and acceleration of systematic land registration programs to prevent future tenure conflicts.